Creep failure and deformation mechanism investigation on a novel single crystal superalloy with various primary ageing temperatures. (March 2022) - Tao, X.P.; Wang, X.G.; Meng, J.; Zhou, Y.Z.; Yang, Y.H.; Liu, J.L.; Liu, J.D.; Li, J.G.; Sun, X.F.
Highlights: Correlation between ageing temperature and creep failure was clarified firstly. γ′ size and γ/γ′ lattice misfit increased as primary ageing temperature raised. As primary aging temperature was 1080 °C, creep life reached to the highest 180 h. Increased elements diffusion rate reduced formation of vacancies and micro-voids. Superislocations were impeded to cut into γ' as ageing temperature was 1080 °C. Abstract: The heat treatment design and optimization of Re-free low-cost single crystal (SX) superalloys, which are commonly regarded as the most practical and economic alloys to manufacture guide vanes and high-pressure turbine blades of aero-engines, are in great demand. In this study, significant adjustments to the primary ageing temperature (PAT) were made, and the synthetic impact of PAT variations from 1050 °C to 1100 °C on the microstructure and creep behaviours in novel Re-free SX alloys was investigated in detail. The results showed that the γ′ size and γ/γ′ lattice misfit increased with increasing PAT, resulting in a reduction in the γ/γ′ interface area and a shift in the morphology of γ' from spherical to cubical. Notably, element diffusion and the resultant coarsening of γ/γ′ structures were facilitated by increasing the PAT. The alloy with 1080 °C PAT showed the longest creep life at 1100 °C/137 MPa, which was approximately 1.5 and 1.2 times that of alloys with PATs of 1050 °C and 1100 °C, respectively. Moreover, as PAT increased, the number of microvoids decreased due to increasing the diffusion rate of elements and hindering the formation of vacancies. When the PAT was too low or too high, the "inland shapes" of the γ′ phase and topological inversion phenomenon occurred during creep, which were detrimental to the creep properties. Furthermore, increasing the PAT resulted in the morphology of γ/γ′ interfacial dislocation networks shifting from sparse waves to fine hexagons and then to coarse hexagons. The dense interfacial dislocation networks in the sample with 1080 °C PAT remarkably impeded superdislocations cutting into γ′ phases. Ultimately, the thermodynamics and kinetics of γ′ formation and growth were also discussed, and the optimum PAT was ascertained to provide further guidance to design and develop Re-free low-cost SX superalloys.